2008
DOI: 10.1021/jp808233e
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Morphologies and Tuning the Related Properties of Nano/Microstructured ZnO Crystallites

Abstract: In this paper, we successfully synthesized three kinds of typical ZnO micro/nanocrystallites including flakes, columns, and pyramids by means of different facile wet chemical routes. The growth environment plays a crucial role in the morphologies of these ZnO micro/nanocrystallites. At the same time, we find that physical/chemical properties of these ZnO samples are dependent on their exposed surface, and the order of gas sensing and photocatalytic efficiency of the ZnO crystal planes is (0001) > {10 (1) over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
255
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 373 publications
(268 citation statements)
references
References 37 publications
10
255
2
1
Order By: Relevance
“…Furthermore, high crystal quality is made available because the material experiences no thermal stress during growth. Associating the XRD results with the photocatalytic degradation of RhB, it is possible to conclude that the growth increase along the c-axis does not provide better photocatalytic activity, contrary to what some authors claim, 2,8,14,19,20 no correlation between these parameters was observed. In analyzing the morphology of the samples and the photocatalytic activity response, it is apparent that a perfect formation of the microstructures composed by nanorods does not necessarily have the highest photocatalytic activity.…”
Section: Xrd Characterizationcontrasting
confidence: 65%
“…Furthermore, high crystal quality is made available because the material experiences no thermal stress during growth. Associating the XRD results with the photocatalytic degradation of RhB, it is possible to conclude that the growth increase along the c-axis does not provide better photocatalytic activity, contrary to what some authors claim, 2,8,14,19,20 no correlation between these parameters was observed. In analyzing the morphology of the samples and the photocatalytic activity response, it is apparent that a perfect formation of the microstructures composed by nanorods does not necessarily have the highest photocatalytic activity.…”
Section: Xrd Characterizationcontrasting
confidence: 65%
“…Freshly calcined samples , with a separation distance between the parallel planes of ~0.24 nm, which is the plane that forms the surfaces of hexagonal pyramids sometimes found at the top of ZnO nanorods [15].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, visible photocatalytic activity will be increased [15]. [8] Under visible illumination ( Figure 7B), the recombination rate also occurs, in less proportion than under UV illumination and the effect of SSA is considered. For MAH samples, the influence of doping process in the photocatalytic activity under UV illumination is negative.…”
Section: Consequently [As] Is Incorporated Into Kinetic Rate (K) Thmentioning
confidence: 99%
“…Therefore, many efforts have been made to synthesize ZnO-based semiconductors with different morphologies for specific devices, such as nanorods, nanobelts, nanosheets, microrod/microtube arrays, quantum dots and other complex hierarchical micro/nanostructures [7,8]. Synthetic routes to ZnO nanoparticles include modified polymeric precursor (MPP) [9], sputtering [10,11], hydrothermal [12], solvothermal [13,14], sol-gel [15,16], ultrasonic irradiation [17], microwave-assisted hydrothermal (MAH) [6,18,19], and zinc-precursor thermal decomposition with free-solvent [20,21] methods.…”
Section: Introductionmentioning
confidence: 99%